Thermomechanobiology as a new research field in soft tissues - Pioletti, Dominique P. (Frontiers in Medical Engineering, 2024)
During intense galloping, the difference in temperature between the external and the central part of an equine superficial digital flexor tendon can be as high as 7°C. Thirty minutes of jogging modifies the temperature in human knee cartilage from 32°C to 37°C. Intrinsic dissipative phenomena related to the viscoelastic behavior of soft tissues have been identified to be primarily responsible for the observed temperature increase, a situation referred to as self-heating in mechanics. While a 5°C increase may be considered negligible from a mechanical point of view in the cartilage at first sight, it can have a significant biological impact. It has been recently proposed that self-heating and the resulting increase of temperature in cartilage following mechanical stimulation can be necessary for its maintenance. This new concept complements the general acceptance that mechanobiology is central to the homeostasis of musculoskeletal tissues. In most biomechanical and biological studies on cartilage or other soft tissues, the temperature is set at 37°C and considered constant, despite human knee cartilage at rest being around 32°C, for example. Therefore, there is a deficit of information on the role and effect of physiological temperature variation induced through mechanical loading in soft tissues, opening a new research avenue that we coin thermomechanobiology.